Ease of Online Ojek Service Grows Consumer Loyalty - Hariyatno, Hariyatno; Wimpertiwi, Dotty; Isanawikrama, Isanawikrama; Bawono, Adhi (Journal the Winners: Economics, Business, Management, and Information System Journal, 2018)
The purpose of this research was to find out why people in the city of Bogor tend to be loyal to ojek online compared to other public transportations. This research conducted in Bogor that used descriptive and verification methods by taking 115 samples of consumers of all fleets motorcycle ojek online in Bogor. The data were taken randomly by using iteration calculation as much as three times. Data analysis used multiple regression analysis. The result of the research shows that the most significant customer loyalty of sub-variable of service quality is reliability. Of the overall population, sub-service quality variables affect customer loyalty 89,5% and the remaining 10,5% is influenced by other factors not examined in this research.